1999
DOI: 10.1046/j.1365-8711.1999.02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Meteoroid stream identification: a new approach -- II. Application to 865 photographic meteor orbits

Abstract: A B S T R A C TThe new criterion D N for meteoroid stream identi®cation, based on variables directly linked to observations, is applied to a set of 865 photographic meteor orbits and the results are compared with those obtained using the well-known and widely used D SH criterion of Southworth & Hawkins, using thresholds for meteor association computed according to Jopek & Froeschle Â. For 15 streams, including the Lyrids, the a Capricornids, the Perseids, the Taurids, the Quadrantids, the Geminids, the Leonids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…As in Jopek et al (1999), after having computed all the mutual distances, we processed them with a cluster analysis computer program implementing an algorithm based on the single neighbour linking technique (Lindblad 1971); the values of the meteor association thresholds were estimated with the method described in Jopek & Froeschlé (1997). The only modification with respect to Jopek et al (1999) has been that, instead of determining the thresholds with a single numerical experiment, 10 of these were carried out; this resulted in obtaining the average thresholds and their standard deviations listed in Table 2.…”
Section: The Distance Function and The Cluster Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As in Jopek et al (1999), after having computed all the mutual distances, we processed them with a cluster analysis computer program implementing an algorithm based on the single neighbour linking technique (Lindblad 1971); the values of the meteor association thresholds were estimated with the method described in Jopek & Froeschlé (1997). The only modification with respect to Jopek et al (1999) has been that, instead of determining the thresholds with a single numerical experiment, 10 of these were carried out; this resulted in obtaining the average thresholds and their standard deviations listed in Table 2.…”
Section: The Distance Function and The Cluster Analysis Methodsmentioning
confidence: 99%
“…Valsecchi, Jopek & Froeschlé (1999) introduced a new distance function D N , based on geocentric quantities directly derived from observations. Then, using the single neighbour linking technique (Lindblad 1971) and values for meteor association thresholds obtained according to the prescriptions of Jopek & Froeschlé (1997), Jopek, Valsecchi & Froeschlé (1999) compared the results obtained with D N to those obtained using the classical distance function D SH of Southworth & Hawkins (1963), on a set of 865 precise photographic meteor radiants. The comparison has shown that D N and D SH give similar results on most streams, but give significantly different ones in the case of ecliptical streams.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This time requirement increases steeply as the data set size is increased. Studies such as Jopek, Valsecchi & Froeschle (1999) have no such problems as they are only dealing with a set of ∼10 3 orbits and therefore can perform 10 3 randomized runs or more with no difficulty.…”
mentioning
confidence: 99%